2009
DOI: 10.1002/ardp.200800221
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antibacterial and Antifungal Activities of Novel 1,2,4‐Triazolium Derivatives

Abstract: A series of novel 1,2,4-triazolium derivatives was synthesized starting from commercially available 1H-1,2,4-triazole, 2,4-dichlorobenzyl chloride, or 2,4-difluorobenzyl bromide. Their antibacterial and antifungal activities were evaluated against Staphylococcus aureus ATCC 29213, Escherichia coli ATCC 25922, Bacillus proteus, Bacillus subtilis, Pseudomonas aeruginosa, Candida albicans ATCC 76615, and Aspergillus fumigatus. All structures of the new compounds were confirmed by NMR, IR, and MS spectra, and elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…The 4-(5-nitro-2-furfurylidene) amino-3-mercapto-5-(substituted)-1,2,4-triazoles (27) 49 and some 1,2,4-triazoles (28) were exhibited antibacterial activity 50 . Antifungal activity of some 1,2,4-triazole has been shown, the 4-substituted-5-aryl-1,2,4-triazoles (29) 51 and 1,2,4-triazolium derivatives (30) were exhibited antifungal activity 52 . Some novel mannich bases derived from 3-(4,6-disubstituted-2-thiomethyl-pyrimidyl)-4-amino-5-mercapto-1,2,4-triazoles (31) 53 and 1,2,4-triazole derivatives (32) were revealed antifungal activity 54 .…”
Section: Antimicrobial and Antifungal Activitymentioning
confidence: 99%
“…The 4-(5-nitro-2-furfurylidene) amino-3-mercapto-5-(substituted)-1,2,4-triazoles (27) 49 and some 1,2,4-triazoles (28) were exhibited antibacterial activity 50 . Antifungal activity of some 1,2,4-triazole has been shown, the 4-substituted-5-aryl-1,2,4-triazoles (29) 51 and 1,2,4-triazolium derivatives (30) were exhibited antifungal activity 52 . Some novel mannich bases derived from 3-(4,6-disubstituted-2-thiomethyl-pyrimidyl)-4-amino-5-mercapto-1,2,4-triazoles (31) 53 and 1,2,4-triazole derivatives (32) were revealed antifungal activity 54 .…”
Section: Antimicrobial and Antifungal Activitymentioning
confidence: 99%
“…The mono-triazole 206 reacted with a series of dihalides, which were commercially available or were prepared by conventional method via bromination of the corresponding precursors, via Nquaternization to readily produce bis-triazolium 207 in good yields of 74-95%. Notably, the reaction temperature obviously affected the formation of target compounds, and only when the temperature was controlled above 80 °C, this reaction would proceed smoothly (Scheme 90) [280,281].…”
Section: N-quaternization Of 124-triazole Ringmentioning
confidence: 99%
“…Many studies from the past had reported that the length of the alkyl groups was an important determinant of antifungal activity (Chandrika, Shrestha, Ngo, & Garneau-Tsodikova, 2016;Luo et al, 2009). Therefore, the effect of the length of the alkyl groups in 1,2,3-triazolium-functionalized starch derivatives on antifungal activity is also evaluated in this paper.…”
Section: Antifungal Activitymentioning
confidence: 99%